Gatunek na usługach doktryny. Ideologia w polsko-enerdowskiej koprodukcji Milcząca gwiazda - Peplinski, Maciej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The East German-Polish co-production The Silent Star (1960, Kurt Maetzig) belongs to the group of early postwar Eastern European science fiction films which still remain barely examined by film and genre historians. The article summarizes the existing research on the film and investigates not only the specific formal character of Maetzig’s unprecedented project, but also the numerous ideological and political motivations which stood behind it.